Spam Classification Using Random Forest Algorithm - Dr Rashmi Agrawal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Natural language Processing (NLP) is an important component of machine learning which have many applications like sentiment analysis, social network analysis, chatbots, text classification, rating of reviews and many more. Researchers are constantly handling the largely available text data now a days and utilising it to apply text mining so that the useful and relevant information can be withdrawn. In this paper, we aim to apply the Random forest technique for text classification. In the first part we will build the word cloud and in the second section we will apply machine learning technique on the spam classification dataset.